2007
DOI: 10.1111/j.1349-7006.2007.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand factor type D domain mutant of SVS‐1/SUSD2, vWDm, induces apoptosis in HeLa cells

Abstract: SVS-1/SUSD2 is a novel gene, which inhibits growth and reverses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…In our studies, analysis of the cellular localization of SUSD2 with fluorescent microscopy revealed a characteristic pattern of distribution in the cell-to-cell contact region. Our observation is in accordance with the [38,39]. A similar pattern of accumulation and biological activity of membrane proteins at cell-to-cell contact sites has also been reported in the case of other adhesion molecules, including E-cadherin, TSLC-1, and nectins [42][43][44][45].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our studies, analysis of the cellular localization of SUSD2 with fluorescent microscopy revealed a characteristic pattern of distribution in the cell-to-cell contact region. Our observation is in accordance with the [38,39]. A similar pattern of accumulation and biological activity of membrane proteins at cell-to-cell contact sites has also been reported in the case of other adhesion molecules, including E-cadherin, TSLC-1, and nectins [42][43][44][45].…”
Section: Discussionsupporting
confidence: 91%
“…Although the function of SUSD2 appears to be similar to that of a number of studied tumor suppressor molecules [38,39], the final assignment of this molecule as a tumor suppressor requires additional studies focusing on genetic/epigenetic alterations and abnormal expression patterns of SUSD2 in tumors. To get more insight into the biological functions of SUSD2 and to identify a potential extracellular ligand, cell-binding assays are in progress.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Two studies by Sugahara et al (6,7) investigated the mouse homolog: SUSD2 (also known as mSVS-1 or SVS-1) was found to be downregulated in activated oncogene-v-K-ras-transformed NIH3T3 cells (Ki3T3 cells), compared with mouse NIH3T3 cells. One of the studies (6) revealed that overexpression of SUSD2 in HT1080 fibrosarcoma cells and HeLa cervical carcinoma cells inhibited clonogenicity, anchorage-independent growth, migration and invasion, via Matrigel assays.…”
Section: Introductionmentioning
confidence: 99%